Regeneration of Teak Forests - Seth, S. K.; Waheed, M. A. (Indian Forester, 1958)
Forests of the teak zone of India are described. Champion's types of Teak Forest are discussed and proposals are made for a revised classification of types, to meet the requirements of intensive management practices at present followed. Factors controlling the occurrence and development of regeneration are detailed and proposals are made for future research to solve the problems of natural and artificial regeneration in the teak zone of India.